Understanding Epigenetic Alterations in Alzheimer's and Parkinson's Disease: Towards Targeted Biomarkers and Therapies - Ciceri, Filippo; Rotllant, David; Maes, Tamara (Current Pharmaceutical Design, 2017)
Background: Alzheimer’s and Parkinson’s disease represent the two most common neurodegenerative disorders, affecting an increasing number of patients worldwide. Population ageing and lack of effective therapies and biomarkers strongly contribute to the socio-economical impact of these conditions. Message and Conclusion: The aim of the review is to present a summary of the discoveries made on the epigenetics of Alzheimer’s and Parkinson’s disease, with a special focus on the recent advances towards the identification of new targeted therapies and biomarkers. Data supporting broad spectrum and selective small-molecule inhibition of enzymes controlling DNA methylation and histone modifications are discussed in the context of Alzheimer’s and Parkinson’s disease. The results obtained from studies performed on patients samples are also mentioned, to provide a picture of the efforts made toward identification of epigenetic-based biomarkers. Finally, given the importance of non-coding RNAs in neurodegeneration, their contribution to Alzheimer’s and Parkinson’s disease will be examined, together with a brief summary of the available miRNA-based biomarker signatures for these two conditions.
Keywords: histone acetylation